HISTORICAL AND ETYMOLOGICAL DEVELOPMENT OF TOPONYMS AND ANTHROPONYMS AND THEIR ROLE IN THE LANGUAGE SYSTEM - Khayitova, Feruza (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The study of proper names constitutes one of the most important branches of modern linguistics because names preserve historical, cultural, ethnic, and cognitive information within the language system. This article investigates the historical and etymological development of toponyms and anthroponyms and analyzes their functional role in linguistic structures. The research applies comparative-historical, etymological, linguocultural, and discourse-analytical approaches to examine naming systems in Turkic, Persian, Arabic, and Indo-European linguistic traditions. The findings demonstrate that proper names function not only as nominative markers but also as repositories of historical memory and ethnocultural identity. Toponyms preserve archaic lexical and phonological forms that disappeared from ordinary vocabulary centuries ago, while anthroponyms reflect religious, political, and sociocultural transformations. The study further reveals that globalization and digital communication increasingly influence modern naming practices, leading to hybridization and semantic simplification of proper names. The article contributes to contemporary onomastic theory by integrating diachronic linguistic analysis with sociolinguistic and cognitive perspectives. The results confirm that proper names represent a stable subsystem within language and provide valuable material for reconstructing historical language stages and intercultural interaction processes.